Crocetin attenuates inflammation and amyloid-β accumulation in APPsw transgenic mice - Zhang, Jin (Immun Ageing, 2018)
BACKGROUND: Crocetin, an agent derived from saffron, has multiple pharmacological properties, such as neuroprotective, anti-oxidant, and anti-inflammatory actions. These properties might benefit the treatment of Alzheimer’s disease (AD). In the present study, we tested whether crocetin attenuates inflammation and amyloid-β (Aβ) accumulation in APPsw transgenic mice, AD mouse models. Cell viability and the levels of Aβ40 and Aβ42 in HeLa cells stably transfected with Swedish mutant APP751 were evaluated. Mice with Swedish mutant APP751 transgene were used as transgenic mouse models of AD, and were orally administrated with crocetin. Aβ protein and inflammatory cytokines were measured with ELISA. NF-κB and P53 were measured with western blot assay. Learning and memory were analyzed with Morris water maze and novel object recognition tests. RESULTS: Crocetin significantly reduced Aβ40 and Aβ42 secretion in Hela cells without effecting cell viability. In AD transgenic mice, crocetin significantly reduced the pro-inflammatory cytokines and enhanced anti-inflammatory cytokine in plasma, suppressed NF-κB activation and P53 expression in the hippocampus, decreased Aβ in various brain areas, and improved learning and memory deficits. CONCLUSION: Crocetin improves Aβ accumulation-induced learning and memory deficit in AD transgenic mice, probably due to its anti-inflammatory and anti-apoptotic functions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12979-018-0132-9) contains supplementary material, which is available to authorized users.